2018
DOI: 10.1021/acsami.8b16692
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Neurotransmitters by Three-Dimensional Laser-Scribed Graphene Grass Electrodes

Abstract: Carbon nanomaterials possess superb properties and have contributed considerably to the advancement of integrated point-of-care chemical and biological sensing devices. Graphene has been widely researched as a signal transducing and sensing material. Here, a grass-like laser-scribed graphene (LSG) was synthesized by direct laser induction on common polyimide plastics. The resulting LSG grass was employed as a disposable electrochemical sensor for the detection of three neurotransmitters, dopamine (DA), epineph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 67 publications
1
33
0
Order By: Relevance
“…Here, we demonstrate a facile approach toward the fabrication of MS‐G nanocomposite photoelectrode by using a direct‐laser‐writing (DLW) technique, which is characterized by the direct and large‐scale conversion of some thermoplastic polymeric sheet to well‐defined 3D porous graphene under transient CO 2 ‐laser induction in an ambient atmosphere without any mask and template . Since the discovery of laser‐induced graphene (LIG) on commercial polyimide films, the high electronic conductivity as well as the large surface areas of LIG has underwent a considerable research progress toward their applications in, for example, supercapacitors and electrochemical sensing . Moreover, impelled by its simplicity and extensive applicability, the DLW technology has been further expanded to a simple and straightforward method that can fabricate heteroatoms‐doped LIG as well as LIG‐metal‐oxides nanocomposite materials .…”
Section: Introductionmentioning
confidence: 99%
“…Here, we demonstrate a facile approach toward the fabrication of MS‐G nanocomposite photoelectrode by using a direct‐laser‐writing (DLW) technique, which is characterized by the direct and large‐scale conversion of some thermoplastic polymeric sheet to well‐defined 3D porous graphene under transient CO 2 ‐laser induction in an ambient atmosphere without any mask and template . Since the discovery of laser‐induced graphene (LIG) on commercial polyimide films, the high electronic conductivity as well as the large surface areas of LIG has underwent a considerable research progress toward their applications in, for example, supercapacitors and electrochemical sensing . Moreover, impelled by its simplicity and extensive applicability, the DLW technology has been further expanded to a simple and straightforward method that can fabricate heteroatoms‐doped LIG as well as LIG‐metal‐oxides nanocomposite materials .…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have reported methods such as oxygen plasma treatment or laser surface glazing as routes to improve repeatability [55][56] . Given that screen-printed carbon might produce intrinsically unreliable electrodes 57 , other carbon-based electrode fabrication technologies, such as laser-scribing of graphene on flexible substrates [58][59] may provide superior alternatives, or electrodes such as gold-coated mylar could be considered.…”
Section: (G) Significance Of the Resultsmentioning
confidence: 99%
“…In past years, due to its extraordinary electrical and optical properties, the graphene has been employed in the field of biochemical sensor such as ionic species detection [ 49 ], glucose monitoring [ 50 ], microRNA detection [ 51 ], DNA detection [ 52 ], and folic acid detection [ 37 ]. However, reliable and scalable biochemical sensor manufacturing and transformation methods are in high demand to fill the existing gap between laboratory research and commercialization [ 53 ]. Direct laser writing will be an ideal fabrication technology and the LIG can be an alternative sensing material or device.…”
Section: Lig-based Sensorsmentioning
confidence: 99%